2017
DOI: 10.5812/jogcr.11945
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pre-Eclampsia Development by Placenta Location: A Simple Predictor

Abstract: Background: Pre-eclampsia complicates 5% to 8% of all pregnancies and annual incidence of pre-eclampsia is about 5% of all pregnancies around the world and is a significant cause of both maternal and fetal mortality and morbidity if left untreated. Objectives: According to previous studies, blood supply distribution within the uterus is not similar in central compared with lateral sites, thus site of implantation and the resulting location of the placenta are likely to have a profound effect on the pregnancy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…On the other hand, the lateral location of the placenta indicates an increased likelihood of developing pe [38], which is also reflected in our results. Our results coincide with those of other authors who have found that the use of mid-trimester ultrasound screening techniques can predict the risk of pe [37]. Some authors link placental laterality and the high risk of hypertension in pregnant women [35,36], which also coincides with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the lateral location of the placenta indicates an increased likelihood of developing pe [38], which is also reflected in our results. Our results coincide with those of other authors who have found that the use of mid-trimester ultrasound screening techniques can predict the risk of pe [37]. Some authors link placental laterality and the high risk of hypertension in pregnant women [35,36], which also coincides with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…18 In a retrospective study by Keshavarz E et al, analysis showed lateral placenta was associated with preeclampsia in 47.6% (20 out of 42) of cases while other locations were associated with preeclampsia in 30% (101 out of 337) (P Value=0.02, Odds ratio: 2.1, 95% confidence interval: 1.1 -4.1). 19 In a study by Pai MV, Pillai J, a total of 426 unselected singleton pregnant women attending the antenatal clinic were included. A total of 71 women developed preeclampsia, of which 52 (74%) had unilaterally located placenta at 20-24 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned data revealed that preeclampsia pregnancies had more antepartum and intrapartum complications than the non-preeclampsia group. 19 Also, caesarean section and low birth weight were more commonly seen in the lateral placenta group compared to the central placenta group.…”
Section: Table 6 Depicts Distribution Of Patients Developing Preeclampsia On the Basis Of Severity Of Diseasementioning
confidence: 90%